Application of bis(glycidyloxy)phenylphosphine oxide as a chain extender for polyamide-6. Issue 40 (7th April 2015) - Wirasaputra, Alvianto; Zhao, Jianqing; Zhu, Yaming; Liu, Shumei; Yuan, Yanchao
Abstract : Figure melt torque of PA6 mixed with different contents of chain extender BGPPO. The addition of small molecule diepoxide (BGPPO) greatly enhanced the melt torque, rheological and mechanical properties of polyamide-6 through chain extension reaction. Abstract : Chain scission of polyamide-6 (PA6) takes place readily during high temperature processing. To prevent possible deterioration in its properties, chain extension of PA6 by the use of bis(glycidyloxy)phenylphosphine oxide (BGPPO), a traditional small molecule flame retardant, has been evaluated in the present study. It was found that the melting torque of PA6 modified by 2.5 minutes' mixing with 1.5 wt% BGPPO was about seven times higher than that of unmodified PA6. As a result of the modification, the proportion of amino and carboxyl end-groups of PA6 was greatly decreased. Accordingly, the tensile, flexural and notched Izod impact strength of the chain-extended PA6 were correspondingly increased, the improvement being superior to that produced using a commercial chain extender. The use of BGPPO for this purpose exemplifies its multifunctional characteristics.